2014
DOI: 10.1016/j.eurpolymj.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative degradation of polylactide (PLA) and its effects on physical and mechanical properties

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractThe thermo-oxidative degradation of polylactide (PLA) films was studied between 70 and 150°C. It was shown that the oxidative degradation of PLA leads to a random chain scission responsible for a reduction of the molar mass. These molar mass changes affect Tg and the degree of crystalllinity, and it was found that Tg decreases according to the Fox-Flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 40 publications
10
115
0
2
Order By: Relevance
“…An amorphous characteristic band at 956 cm −1 shows a decrease in intensity in the blank and grafted films, compared to neat PLA. Simultaneously, a sharp PLA -crystal's band appears at 921 cm −1 in the 2 treated films [29,30]. The results firmly ensure that there is a significant transformation of amorphous phase to crystalline domains, due to conformational changes induced by newly formed -OH and -COOH terminals, as observed in GPC results.…”
Section: Ftir Spectroscopysupporting
confidence: 78%
“…An amorphous characteristic band at 956 cm −1 shows a decrease in intensity in the blank and grafted films, compared to neat PLA. Simultaneously, a sharp PLA -crystal's band appears at 921 cm −1 in the 2 treated films [29,30]. The results firmly ensure that there is a significant transformation of amorphous phase to crystalline domains, due to conformational changes induced by newly formed -OH and -COOH terminals, as observed in GPC results.…”
Section: Ftir Spectroscopysupporting
confidence: 78%
“…Recently, Fayolle and coworkers have reported PLA aging in atmospheric conditions with the absence of water and UV light [220]. They Ethylene oxide Low temperature range Lengthy process due to degassing residues are toxic studied the oxidative degradation of PLA induced at moderate temperatures (i.e.…”
Section: Agingmentioning
confidence: 99%
“…These results come in agreement with some common behaviors observed during polyolefin oxidative aging. Consequently, knowing the chain scission kinetics, it will be possible to predict the embrittlement time, in other words the time when Mn is below 40 kg/mol: this time is around 150 h, 250 h and 500 h for the PLA aged at 150, 130 and 100°C respectively [220].…”
Section: Agingmentioning
confidence: 99%
“…The thermal degradation of polylactide in the presence of oxygen was studied between 70 and 150°C where a reduction of molar mass resulting in variation in glass transition temperature, degree of crystallinity was observed. This work also derived a relationship between molar mass and strain at break and concluded that chain scission process is responsible for decrease of molecular weight of PLA (Rasselet et al 2014). A study to determine the crystal structure of moulding grade polylactide revealed that polylactide achieved crystallinity up to 40% when annealed at 100-140°C for 10 min (Tábi et al 2010).…”
Section: Introductionmentioning
confidence: 99%